An Analysis of Taboo Words in Deadpool & Wolverine Movie - Bramantyo, Agiel; Rahayu Sugiharti, Dona (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
The objectives of this research are to find out the type of taboo words and to explains its functions. This research employed the theory by Allan & Burridge (2006) to classify the type of taboo word and to explain the function based on the context of the movie. Allan & Burridge (2006) reveal that there are four types of taboo word; sexual, food, addressing sacred being, and diseases and death. All of that have functions either to release tension, humor, challenging authority, or solidifying social bond. This research employs a qualitative narrative method to analyze the taboo words found in the movie. The result indicates that there are 197 data regarding the use of taboo words in Deadpool & Wolverine movie. These data are classified into three types of taboo words. They are sexual, addressing sacred being, and diseases and death. The sexual type becomes the most dominant type in the movie uttered by Deadpool. This research also shows that all functions of taboo words are used in the movie. Releasing tension becomes the most frequent function to occur. The frequent use of this functions reflects the characters struggle on coping with the collapsing world. This research shows that taboo words serves an important sociolinguistics functions beyond mere vulgarity.In addition, this research offers a valuable insights for understanding language use in media and its reflection of real-life social and emotional dynamics. Keywords: Deadpool & Wolverine movie, qualitative research, sociolinguistics, taboo words